Aspek Hukum Kewenangan Notaris Dalam Kontrak Kerjasama Pengadaan Tanah Pada Kegiatan Eksplorasi Usaha Hulu Migas - Ahmad Fachrisal Lubis (Magister Kenotariatan, Universitas Jambi, 2019)
This research is research that examines the Legal Aspects Authority Notary In Cooperation Contract Land Acquisition In Exploration Upstream Oil and Gas Issues raised in this study describes how the authority of the notary as a deed authentic and do in the procurement of land for business activities of exploration upstream oil and in terms of what the notary has authority in the contract procurement of land for business activities upstream oil and gas exploration. This study uses normative measures description, systematization and explanation of the content of positive law in depth by using a concept, approach to law and systematic analysis of synchronization. This study aims to assess and analyze in depth about the authority of the notary deed as authentic and do in the procurement of land for business activities upstream oil and gas exploration. In addition to know and understand and analyze in depth on what the notary has authority in the contract procurement of land for business activities upstream oil and gas exploration. The results showed that the Notary is authorized to make the authentic act of all deeds, agreements, and provisions required by legislation and or desired by the stakeholders to be declared in an authentic deed, including a deed of land acquisition for the business activities of the upstream oil and gas, ensure certainty the date of deed, saving certificates, copies and official copies, all of it throughout the making of the deed was not assigned or excluded to other officials or others established by law. The authority was necessary because of the need for written evidence in the form of an authentic deed to the rule of law in a variety of economic and social relations, both nationally, regionally and globally, through the authentic act clearly define the rights and obligations, ensure legal certainty. Notary deed authentic authority to make such a deed on the contract land acquisition for upstream oil and gas business activities essentially contains the formal correctness notified in accordance with what the parties to the notary, as well as providing access to information, including access to legislation. In his capacity as a deed officials related to civil law, in accordance with the authority granted by the State / Government, which makes authentic act as written evidence directly related to the law of evidence.